Parenting Interventions for ADHD: A Systematic Literature Review and Meta-Analysis. (October 2015) - Coates, Janine; Taylor, John A.; Sayal, Kapil
Objective: To evaluate the evidence base relating to the effectiveness of parent-administered behavioral interventions for ADHD.Method: A systematic review of randomized controlled trials or non-randomized but adequately controlled trials for children with ADHD or high levels of ADHD symptoms was carried out across multiple databases. For meta-analyses, the most proximal ratings of child symptoms were used as the primary outcome measure.Results: Eleven studies met inclusion criteria (603 children, age range = 33-144 months). Parenting interventions were associated with reduction in ADHD symptoms (Standardized Mean Difference [SMD] = 0.68; 95% confidence interval [CI] [0.32, 1.04]). There was no evidence of attenuation of effectiveness after excluding studies where medication was also used. Parenting interventions were also effective for comorbid conduct problems (SMD = 0.59; 95% CI [0.29, 0.90]) and parenting self-esteem (SMD = 0.93; 95% CI [0.48, 1.39]).Conclusion: These findings support clinical practice guidelines and suggest that parenting interventions are effective. There is a need to ensure the availability of parenting interventions in community settings.